National Archives of Fiji a systems analysis - Ravatu, Semiti Gaunavinaka 1959- (1998)
1. Internal analysis which covered 15 staff members. Their analysis with procedures, objectives of tasks, workflows, attitudes, skills, education, etc. together with observations and interviews during the course of work. A set of structured questionnaires were also used to measure their opinions on the evaluation.
and Students 34(20
and Students 52(20
Civil servants 32(12
Civil Servants 32(19
Researchers (overseas) 12(5
Researchers (overseas) 9(5
These covered the services offered by the National Archives of Fiji.
1. The assessment of the present status of the National Archives of Fiji in terms of: administration and management; staff/personnel, facilities/equipment, materials and supply, collection and holding were seen as "bad" to "very bad".
1. The elevation of the Archivist as the new head of the National Archives. He has the right qualifications, experience, skills and knowledge to lead this precious institution.
2. A reorganisation of the whole institution to allow for tasks to be done faster and more appropriately. Clear lines of authority and communication within the organisation ought to be established.
2. External analysis which covered the external user categories; Researchers (local) 161 (63
2. The different types of services provided by the institution were also perceived as "bad". The cause of these problems seems to relate to each other. For instance, it takes so much time to locate needed information simply because indexing is not properly done. High recall seems to be accepted by staff as good instead of high precision.
3. A list of training needs has been also to improve staff knowledge and technical skills within the organisation.
3. A user study was also conducted to define users' needs and behavior with the following categories; Researchers (local) 94(56
3. The role of the National Archives of Fiji was perceived as "inadequate."
4. A suggested general systems design has been designed to cater to the organisation in the light of the findings above.
4. The users and staff alike perceived the use of information technology as "very much needed" in the National Archives of Fiji.
Archives are the records of organizations, created or accumulated in the course of daily activities, and saved by the creator because they may be useful for continuing administration or for later research.Although archives are retained by the organizations that created them, they may have as much value for researchers outside the organization, as part of the cultural heritage linking past to present.
It will also be a tremendous risk on the archival documents if proper care and storage are not done now. The people of Fiji will stand to lose the most if the status of the National Archives is further ignored.
The findings of the study show "inadequacy" in the equipping of the National Archives of Fiji. The present status as highlighted by the staff were either "bad" or "very bad". The need for a better system was also seen from the ratings of the total population surveyed that the use of information technology can improve information retrieval for internal and external users. Specifically the study came out with the following findings
The highlights of the recommendations to improve the National Archives of Fiji are
The study concluded that the National Archives of Fiji has been neglected for too long that it is neither properly equipped, nor properly staffed with the right people and with the right qualifications and experience. While the staff have tried to function with the limited resources they have, leadership does have an impact on their work. Unless the responsible authorities act now, the users of these resources will not be deprived of access to valuable information.
This study is a systems analysis of the National Archives of Fiji. During the analysis period, three sets of data were gathered and analyzed. These were as follows
Computer print out.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: National Archives of Fiji; Archives -- Fiji